Minds, Intrinsic Properties, and Madhyamaka Buddhism - Rockwell, Teed (2009)
Abstract. Certain philosophers and scientists have noticed that there are data that do not seem to fit with the traditional view known as the Mind/Brain Identity theory (MBI). This has inspired a new theory about the mind known as the Hypothesis of Extended Cognition (HEC). Now there is a growing controversy over whether these data actually require extending the mind out beyond the brain. Such arguments, despite their empirical diversity, have an underlying form. They all are disputes over where to draw the line between intrinsic and relational causal powers. The second-century Buddhist philosopher Nagarjuna deals with similar issues when he argues for a middle way between the two positions that were known in his time by the terms eternalism and nihilism. Eternalism, like MBI, asserts that the mind is a permanent enduring substance (although the two theories disagree as to how long mind endures). Nihilism argued that the mind had no intrinsic existence, and today some argue that HEC could lead us to a similar conclusion. Nagarjuna's argument for a middle way between these two extremes is similar to an argument that can be made for HEC. We can accept that neither the brain nor any other single physical item is identical to the mind without falling down the slippery slope that leads to “The mind does not really exist, and therefore we are one with everything.” Nagarjuna was correct to say that the mind has conventional reality—that the mind exists even though there is no sharp border between the mind and the world.
Keywords: Nagarjuna; mind/brain identity theory; hypothesis of extended cognition; extended mind